2020
DOI: 10.18510/hssr.2020.8121
|View full text |Cite
|
Sign up to set email alerts
|

Hope and Optimism on the Future of Indonesian Islam: A Discourse Analysis of Pesantren in Pantura

Abstract: Purpose of the study: This study aimed to understand the meaning perception of hope and optimism about the future of Islam in Indonesia. Methodology: The study used discourse analysis, the collection of data obtained through observation, in-depth interview and documentation. Main Findings: Results of the study showed confidence in the future of Indonesian Islam is based on optimism. Applications of this study: the research has done in pesantren Tarbiyatut Tholabah Kranji. The participant of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Thus far, Indonesia has been a part of optimism studies conducted in 95% of the world's population (Gallagher et al, 2013). A study found that optimism and its relation to the educational context could be a new Indonesian ideology (Gellert, 2015), where optimism is also considered to be "the future of Indonesian Muslim students" (Muniroh et al, 2020). Furthermore, a descriptive study reported that Indonesian students have a moderate to high level of optimism (Augustiya et al, 2019;Umboh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, Indonesia has been a part of optimism studies conducted in 95% of the world's population (Gallagher et al, 2013). A study found that optimism and its relation to the educational context could be a new Indonesian ideology (Gellert, 2015), where optimism is also considered to be "the future of Indonesian Muslim students" (Muniroh et al, 2020). Furthermore, a descriptive study reported that Indonesian students have a moderate to high level of optimism (Augustiya et al, 2019;Umboh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is politically considered to be able to open the arena of constellation between religions on the one hand and between religions and countries on the other. This concern is not strong enough because religious tolerance in Indonesia is very good (Ghazali & Hasanah, 2020) (Muniroh et al, 2020). This article will examine the transformation of Islamic law into Indonesian national law in the Reform Era.…”
Section: Introductionmentioning
confidence: 99%